Phylogenetic relationships within Pseudamnicola Paulucci, 1878 (Caenogastropoda: Truncatelloidea) indicate two independent dispersal events from different continents to the Balearic Islands. Issue 4 (18th May 2020) - Boulaassafer, Khadija; Ghamizi, Mohamed; Machordom, Annie; Delicado, Diana
Abstract : Until recently, the evolutionary origin of aquatic organisms in the Balearic archipelago (western Mediterranean) had been scarcely addressed. The freshwater gastropod genus Pseudamnicola Paulucci, 1878 (Hydrobiidae), consisting of ∼60 species in the Mediterranean area, is widely distributed across the major islands of Majorca and Minorca. From phylogenetic datasets of limited geographic coverage, a recent well-supported split has been inferred between the Minorca and Iberian Pseudamnicola species, but the phylogenetic position of the Majorca clade composed of three species remained uncertain. In this study, we extend published sequence data for the COI and 16S rRNA mitochondrial genes and the 28S rRNA nuclear gene in western Mediterranean populations of Pseudamnicola with homologous sequences from individuals of the non-surveyed region of Morocco to assess the origin of the Balearic species from a wider geographic perspective. Our maximum likelihood and Bayesian inference analyses recovered a strongly supported clade comprising the Majorcan species and four phylogenetic lineages in Morocco, two of which are new to science (described here as P. ramosae sp. nov. and P. ouarzazatensis sp. nov.). Dating the nodes using an external molecular clock rate, younger ages were estimated for the Majorcan species (∼1 Mya) than for the Moroccan ones (∼5 Mya), which were still younger than the formation of the Balearic Islands (∼30 Mya). An independent well-supported clade grouped the Minorca and Iberian species diverging at ∼4 Mya. Thus, we found two independent evolutionary origins within the Balearic archipelago likely attributable to long-distance dispersal events from the African and Eurasian continents. http://zoobank.org :pub:24D17C1D-4A42-4722-9867-D8D84465F55A http://zoobank.org :act:85EC4DF1-9BFA-4B28-B3F2-C091212AFCF1 http://zoobank.org :act:C790EAC6-F22B-489A-93EB-CABF9EEAF282